Orbital Fractures - Zhou, Peiran; Chambers, Christopher B. (Seminars in Plastic Surgery, 2021)
Orbital fractures are common in facial trauma and can be a challenge to treat. Understanding anatomy of the orbit, the clinical evaluation, indications for surgery, surgical approaches, complications, and postoperative are essential in providing appropriate treatment for patients who have sustained orbital fractures. In this article, the authors review the diagnostic evaluation, acute management, treatment options, and common complications of orbital fractures, as well as recent advancements in orbital fracture repairs.
Keywords: orbital fracture; evaluation; management; complications